GAGASAN UJI TEORI EMPIRIS MELALUI FALSIFIKASI (Analisis Pemikiran Karl Popper dalam Filsafat Ilmu) - Haryono, Dedi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2014)
Karl Popper had tried to make clearity of a theory production leading to subjectivitythat will effect to serious mistake, the observer of science undifided from phylosophy, instead, it had given rightly of science itself, Without through suitable research. In order not to get influence of this thing, so the principle of science must be inherent with falsification, included experiment and hypothesis. The falsiability was not received on generally. it was a basic of the science activities. The statement and theory which were gotten empiric or positive logic, finally, It must be concluded, they are statement and theory. It means that the statement and theory itself must own final conclusion (conclusively decidable atau conclusive verification). If the statement and theory themselves could not get the target, so, both of them are no mean.